RESPON MASYARAKAT TERHADAP PROGRAM VAKSINASI COVID-19 DI KABUPATEN POSO PROVINSI SULAWESI TENGAH - Aepu, Sitti Hajar N.; Bakari, Yulianti; Claudia, Jeane (Kinesik, 2022)
This study discusses vaccination, where the government's efforts to protect the health of its citizens from the Covid-19 virus are carried out simultaneously in Indonesia. This study aims to describe and analyze the extent of public knowledge and experience of the Covid-19 vaccination program and the response shown by the community to accept or reject the vaccination. Qualitative research method with the stages of observation and in-depth interviews as well as conducting a literature review related to the research focus. The rhesults showed that the knowledge and experience of the people of Moengko Baru Village about vaccination was still lacking and varied, where more information was obtained from social media, mass media so that they believed in hoax news circulating and would indirectly affect the response to behavior, attitudes and actions in vaccinating. However, some people already have good knowledge of the vaccination and are willing to be vaccinated for health and for immunity against diseases/viruses. The Government of Poso Regency has carried out a socialization program in the community so that the public better understands the importance of vaccination in the formation of herd immunity or group immunity.